Evaluasi Pengaruh Konsentrasi Pati Biji Cempedak (Artocarpus champeden) sebagai Bahan Pengisi pada Formulasi Tablet Paracetamol - Noval Noval; Rizka Appriliani; Husda Oktaviannoor (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2021)
Cempedak plants are widely distributed in Indonesia, one of which is Kalimantan. Cempedak is a tropical plant, so its potential can be used as an additive in the manufacture of pharmaceutical preparations. Previous studies used cempedak seed starch as a binding agent in tablet formulations. This study aims to determine the effect of variations in concentration and optimum concentration of Cempedak seed starch (Artocarpus champeden) as a filler for Paracetamol tablets. The study used a True Experimental Design design with a posttest-only control group design. Making tablets using the wet granulation method. Data analysis used the one-way ANOVA test followed by the LSD test and the Kruskal-Wallis H test which continued with the Mann Whitney Test as a derivative test of the one-way ANOVA. Granule evaluation includes organoleptic, flow properties, tapping test, and stationary angle test. The results of the evaluation of the granules produced granules produced from each formulation are in accordance with the requirements. Tablet evaluation included organoleptic, uniformity in weight, the hardness of tablet, friability, and disintegration time. The results of the tablet evaluation showed that the maximum concentration of cempedak seeds was found in F1 because it showed the evaluation results that were in accordance with the requirements. In evaluating the uniformity of weight and hardness of tablets with the Kruskal Wallis H test and the Mann Whitney test, the results show that there are differences in each formula with a P-value <0.05. The results of the evaluation of tablet friability and disintegration time with one-way ANOVA test and LSD test showed differences in each formula with a P-value <0.05. Cempedak seed starch (Artocarpus champeden) can be used as a filler in the loading of Paracetamol tablets by the wet granulation method.